Strategi Komunikasi KPI (Komisi Penyiaran Informasi) dalam Mensosialisasikan TV Digital - Amanda Eka Nur Oktaviani; Aprianto Arohim Nugraha; Endang Safitri; Siti Munawaroh; Vika Devinta Sari (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
The aim of this research is to introduce the public to the digitalization of broadcasting, especially television in Indonesia and DKI Jakarta in particular. Currently we are entering the era of digitalization of broadcasting marked by ASO. For this reason, KPID DKI Jakarta is holding this JBeX activity, one aim is to provide sufficient information to the public regarding digitalization of broadcasting. Because usually when we talk about digital, people only know about digital internet. The method used is descriptive qualitative research with case studies. The information collection method used includes in-depth interviews and obtaining other information such as documents and other data sources related to this research. Based on the results of the research that has been carried out, the researchers then held a discussion regarding the results of the data obtained regarding KPI communication strategies in socializing Digital TV. In this research, researchers used persuasive theory and Lasswell’s communication model. The result was that the Indonesian Broadcasting Commission built additional towers to strengthen the signal. This is proven by the large number of people who switch to digital TV channels rather than other TV channels. The Indonesian Broadcasting Commission also verifies digital TV data in maximizing broadcast signals. These improvements make the picture and sound quality much better compared to analog TV broadcasts.